Comparison of kick exercises using feet full inside and back of the foot for shooting accuracy - Sufyansyah, Taufiq; Widyastuti, Suci Rahayu; Suganda, Mikkey Anggara (Universitas Tanjungpura, 2022)
This study aims to determine the effect of shooting practice with the inner instep and full instep on the shooting accuracy of students of the Porseka Football School (SSB), Kaliwulu Village, Plered District, Cirebon Regency. Football students in this study were limited to 13-14 years old. This study uses an experimental method with a